Interphase engineering of reactive metal surfaces using ionic liquids and deep eutectic solvents—from corrosion control to next-generation batteries. (December 2017) - Forsyth, Maria; Howlett, Patrick; Somers, Anthony; MacFarlane, Douglas; Basile, Andrew
Abstract Ionic liquids are unique solvents composed entirely of ions and have recently been considered for applications ranging from synthesis, separations, electrochemical devices, tribology and corrosion. In this perspective, we summarise the literature, and look at the future prospects, surrounding the use of ionic liquids in the engineering of interphases to control charge transport thereby leading to improved performance of high-energy density batteries, including Mg, Li and Na metal as well as corrosion protection of reactive engineering alloys, such as aluminium, magnesium and steel alloys. The ability to create task-specific ionic liquids by controlling the chemistry of either the anion or the cation means that interphases can be engineered for specific substrates and applications. Thus far, fluorine containing anions, such as bis(trifluoromethane) sulfonamide and its analogues, have been favoured for controlling the conductive solid–electrolyte interphase layer on Li and Na, while ionic liquids containing organophosphate anions have been used to form nanometre thick protective interphases on Mg alloys. Recently, ionic liquids based on carboxylate anions have also been shown to provide excellent corrosion inhibition for steel. In the search for cost-effective solutions, a relatively new class of ionic liquids, termed deep eutectic solvents, have also been explored as potential media for controlling surface films on reactive metals. The deep eutectic solvents class of ionic liquid materials offers many possible combinations of chemistry that can be targeted to produce desired properties in this context.